2004
DOI: 10.1103/physrevlett.93.176402
|View full text |Cite
|
Sign up to set email alerts
|

Spin Splitting Induced by Spin-Orbit Interaction in Chiral Nanotubes

Abstract: We show that chiral tubes present spin splitting at the Fermi level in the absence of a magnetic field, whereas achiral tubes preserve spin degeneracy, as evidenced by tight-binding electronic structure calculations with the inclusion of spin-orbit interaction. These remarkably different behaviors of chiral and nonchiral nanotubes have a symmetry origin, which may provide a global explanation to recently reported spin-dependent transport experiments which were in apparent contradiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
88
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 26 publications
8
88
0
Order By: Relevance
“…Only recently was it proven experimentally 9 that in the spectrum of ultraclean CNT's, the effects of this coupling between spin and orbital degrees of freedom are clearly visible. This observation is in agreement with previous theoretical predictions, [10][11][12] which argued that SOI could be significant in CNT's due to their curvature. Understanding the effects of this coupling on the spectrum of CNT's is essential for the successful manipulation of the different degrees of freedom of these systems.…”
Section: Introductionsupporting
confidence: 83%
“…Only recently was it proven experimentally 9 that in the spectrum of ultraclean CNT's, the effects of this coupling between spin and orbital degrees of freedom are clearly visible. This observation is in agreement with previous theoretical predictions, [10][11][12] which argued that SOI could be significant in CNT's due to their curvature. Understanding the effects of this coupling on the spectrum of CNT's is essential for the successful manipulation of the different degrees of freedom of these systems.…”
Section: Introductionsupporting
confidence: 83%
“…Band splitting was found considering surface curvature effects [9], as well as in the electron spin resonance spectra of achiral CNTs derived by low-energy theory [10]. In an earlier work, we showed that the inclusion of the full lattice symmetry is essential for deriving spin-orbit (SO) effects in CNTs [11]. Employing an empirical tightbinding model, we demonstrated an intrinsic symmetry dependence of SOI effects.…”
mentioning
confidence: 99%
“…18 While the curvature-induced SO coupling was envisioned previously for semiconductors, 25,26 for nanotubes it is the dominant mechanism. It was Ando 27 and others 28,29 who developed the first theories of SO coupling in nanotubes. More recent theoretical investigations extended this work by including the and bands in full as well as the curved bonds between neighboring atoms.…”
Section: Introductionmentioning
confidence: 99%